2017
DOI: 10.1111/spol.12345
|View full text |Cite
|
Sign up to set email alerts
|

‘Replacement Care’ for Working Carers? A Longitudinal Study in England, 2013–15

Abstract: In the context of rising need for long-term care, reconciling unpaid care and carers' employment is becoming an important social issue. In England, there is increasing policy emphasis on paid services for the person cared for, sometimes known as 'replacement care', to support working carers. Previous research has found an association between 'replacement care' and carers' employment. However, more information is needed on potential causal connections between services and carers' employment. This mixed methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 17 publications
(21 reference statements)
2
54
0
Order By: Relevance
“…Formal services never could or should completely replace the important and personalised support provided by mental health carers (Diminic et al, ). However, improving the effectiveness and accessibility of support services for both people with mental illness and their carers is likely to enable carers some respite and help them to sustain multiple roles of caring and paid work more easily (Lilly et al, ; Pickard, ; Pickard et al, ). Assisting carers with an intensive support role to better balance their employment and caring responsibilities is likely to have both economic benefits and significant benefits to carers’ own financial stability and quality of life (Carers Australia, ; Jacobs et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Formal services never could or should completely replace the important and personalised support provided by mental health carers (Diminic et al, ). However, improving the effectiveness and accessibility of support services for both people with mental illness and their carers is likely to enable carers some respite and help them to sustain multiple roles of caring and paid work more easily (Lilly et al, ; Pickard, ; Pickard et al, ). Assisting carers with an intensive support role to better balance their employment and caring responsibilities is likely to have both economic benefits and significant benefits to carers’ own financial stability and quality of life (Carers Australia, ; Jacobs et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the 2015 SDAC was cross‐sectional, it was not possible to identify a causal association between caring hours and employment; carers who provide a high number of support hours may need to exit the workforce, but also carers who are not employed may be able to provide more support. Longitudinal studies have shown that intense caring hours for working carers do lead to a significant subsequent risk of leaving the workforce (King & Pickard, ; Leigh, ; Pickard et al, ). We did not explore whether characteristics of the carer's original employer or job role were related to their current employment status; this would be an interesting area for further research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations